ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENERIMAAN KAS PADA PT.RIPA MITRASEJAHTERA MANDIRI DI MUARA MUNTAI - Permadi, Angga Bagus (EKONOMIA, 2018)
A good accounting information system is expected to produce a good report and a good report will be analyzed and used to make decisions that are very important for the company itself for the future, where the financial statements have usefulness, both internally and externally, ie internal to provide management accountability to company owners and externally the financial statements will be used as a decision making for a company. The system of sales and cash receipts is a core system that has a major influence on the success of a company because sales are business activities carried out by the company to be able to obtain profits while cash receipts are an initial measure of profit received by the company which according to its characteristics and functions, cash is an easy tool to misuse by parties who are not responsible.The purpose of this paper is to determine the sales accounting system and cash receipts at PT. Ripa Mitrasejahtera Mandiri is seen from the elements of internal control.The research method used is qualitative research. Qualitative research methods are an approach or search to explore and understand a central phenomenon. To understand the central symptoms, the researcher interviewed the study participants or participants by asking general and rather broad questions. The analytical tool used in this study is the distribution of questionnaires and the use of flowcharts according to the source.Based on the results of the analysis previously stated, it can be seen that the implementation of the sales accounting system and cash receipts at PT. Ripa Mitrasejahtera Mandiri in Muara muntai runs well on the sales section as evidenced by the results of the analysis that get a relative value of 70% means categorized "Appropriate" then the hypothesis is "rejected" while in the cash receipt section gets a relative value of 50% means categorized "Not suitable" then the hypothesis is "accepted", although it still provides the possibility for certain parties in the company to take irregularities, because the sales accounting information system and cash receipts still have weaknesses in some elements of control.